1992
DOI: 10.1302/0301-620x.74b3.1587893
|View full text |Cite
|
Sign up to set email alerts
|

Closed division of the flexor tendon sheath for trigger finger

Abstract: Closed tenotomy was used to treat triggering of the fingers and thumb in 54 patients. In 56 digits the method was successful; in seven it was a simple matter to proceed to open tenotomy. With experience, the closed procedure can be completed within minutes without risk of damaging the digital nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…7 The authors then dissected the fingers and found that the A1 pulley was not completely released in 32% of fingers. We believe that the low percentage of complete release of the A1 pulley in their study may be attributed to the use of insufficiently precise parameters, and that the use of more precise palmar surface landmarks such as measure A may yield more satisfactory results in percutaneous release with needles.…”
Section: Discussionmentioning
confidence: 99%
“…7 The authors then dissected the fingers and found that the A1 pulley was not completely released in 32% of fingers. We believe that the low percentage of complete release of the A1 pulley in their study may be attributed to the use of insufficiently precise parameters, and that the use of more precise palmar surface landmarks such as measure A may yield more satisfactory results in percutaneous release with needles.…”
Section: Discussionmentioning
confidence: 99%
“…The "blind" percutaneous technique uses surface anatomical landmarks [12][13][14][15][16][17][18][19][20][21][22]. Although it has been shown to be safe, it is complicated by incomplete release or the need to convert to an open release, which has been reported in up to 11% of cases [13,16,23].…”
Section: Discussionmentioning
confidence: 99%
“…Here, its tip is seen transecting the A1 pulley. Note how the operator can ensure that it remains dead centre over the flexor tendon under sonographic guidance during the procedure, particularly the digital nerves which have been shown to have a variable course in cadaveric studies [12][13][14][15][16][17][18][19][20][21][22]. Several studies suggest the variation in digital nerve position in the thumb, index and little finger puts non-image-guided percutaneous release at risk of complications [6,8,12,16,20,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonographic monitoring with a special cutting instrument, kept deadcentre over the flexor tendon sheath (Ha et al, 2001;Lyu, 1992) and performed with a custom-made needle Clinical picture (C) and transverse sections of sonograms (D) of the long finger with grade IV trigger digit after the procedure. mur et al, 1998;Patel and Moradia, 1997;Tanaka et al, 1990) allowed observation during the division.…”
Section: Article In Pressmentioning
confidence: 99%